2016
DOI: 10.1039/c6fd00004e
|View full text |Cite
|
Sign up to set email alerts
|

The “Parade Blue”: effects of short-term emission control on aerosol chemistry

Abstract: The strict control on emissions implemented in Beijing, China, during the 2015 China Victory Day Parade (V-day Parade) to commemorate the 70(th) Anniversary of Victory in World War II, provided a good opportunity to investigate the relationship between emission sources and aerosol chemistry in a heavily polluted megacity. From August 11 to September 3, 2015, an Aerosol Chemical Speciation Monitor was deployed in urban Beijing, together with other collocated instruments, for the real-time measurement of submicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…For observations in Beijing, the total PM 1 mass was simultaneously measured using a PM-714 monitor (Kimoto Electric Co., Ltd., Japan) based on the β-ray absorption method (Li et al, 2016). Meteorological conditions, including temperature, RH, wind speed, and wind direction, were reported by an automatic meteorological observation instrument (Mi-los520, VAISALA Inc., Finland).…”
Section: Sampling Site and Instrumentationmentioning
confidence: 99%
“…For observations in Beijing, the total PM 1 mass was simultaneously measured using a PM-714 monitor (Kimoto Electric Co., Ltd., Japan) based on the β-ray absorption method (Li et al, 2016). Meteorological conditions, including temperature, RH, wind speed, and wind direction, were reported by an automatic meteorological observation instrument (Mi-los520, VAISALA Inc., Finland).…”
Section: Sampling Site and Instrumentationmentioning
confidence: 99%
“…The answer is true. China has succeeded in various emission reduction campaigns such as during the 2014 Asia-Pacific Economic Cooperation (APEC) meeting and the 2015 China Victory Day Parade Wang et al, 2017;Xue et al, 2018;Li et al, 2016). In order to reduce anthropogenic emission, factories, industrial plants, construction sites, and gas stations was temporarily closed in and around Beijing, vehicles were kept off the roads, and 6-days mandatory holidays were brought to state-owned enterprises, local government offices and educational institutions (Sun et al, 2016;Wang et al, 2016;Li et al, 2017d;Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2012) found that near-surface SO 2 concentrations in the PRD region during the Asian Games were lower than in the same period in previous years using OMI data. Huang et al (2015) found that the tropospheric NO 2 concentration in North China Plain during APEC in 2014 was 47% lower than that in the same period of the previous 3 years; Li et al (2016) found that the total PM 1 mass was reduced by 52–57% during the 2015 China Victory Day Parade (V-day Parade) by excluding the effects of meteorological parameters. Compared with those events, the COVID-19 lockdown exerts much more evident influences on the society in terms of both persistence and strength.…”
Section: Introductionmentioning
confidence: 99%